Air guitar using MyDAQ - Neo, Danny (2013)
In the past, many ideas are birth forth through innovation, designs and significant budget poured in to develop new and cool products to improve life and change the way people live. In the rapid development of technology in the world today, processors and computers are getting faster and cheaper. Thus it is now easier for any one to develop new product with limited budget. In this project we will be using MyDAQ, a type of embedded system, which basically operate as computer system used for a particular purpose.